MATHEMATICAL FORMALIZATION OF SIMPLE WORD-COMBINATIONS USING THE ALGEBRA OF FINITE PEDICATES (ON THE EXAMPLE OF THE UKRAINIAN LANGUAGE) - Якімова, Наталія (Modern engineering and innovative technologies, 2025)
In modern linguistics, the problem of computer processing of natural language is becoming more and more relevant. This is related to the rapid development of artificial intelligence systems, the creation of various dialog systems that involve the use of a